Regulation of the urea cycle by CPS1 O-GlcNAcylation in response to dietary restriction and aging. (14th March 2022) - Wu, Jing; Liu, Jiayu; Lapenta, Kalina; Desrouleaux, Reina; Li, Min-Dian; Yang, Xiaoyong
Abstract: O -linked N -acetyl-glucosamine glycosylation ( O -GlcNAcylation) of intracellular proteins is a dynamic process broadly implicated in age-related disease, yet it remains uncharacterized whether and how O -GlcNAcylation contributes to the natural aging process. O -GlcNAc transferase (OGT) and the opposing enzyme O -GlcNAcase (OGA) control this nutrient-sensing protein modification in cells. Here, we show that global O -GlcNAc levels are increased in multiple tissues of aged mice. In aged liver, carbamoyl phosphate synthetase 1 (CPS1) is among the most heavily O -GlcNAcylated proteins. CPS1 O -GlcNAcylation is reversed by calorie restriction and is sensitive to genetic and pharmacological manipulations of the O -GlcNAc pathway. High glucose stimulates CPS1 O -GlcNAcylation and inhibits CPS1 activity. Liver-specific deletion of OGT potentiates CPS1 activity and renders CPS1 irresponsive to further stimulation by a prolonged fasting. Our results identify CPS1 O -GlcNAcylation as a key nutrient-sensing regulatory step in the urea cycle during aging and dietary restriction, implying a role for mitochondrial O -GlcNAcylation in nutritional regulation of longevity.